2014
DOI: 10.3748/wjg.v20.i16.4607
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection and diabetes: Is it a myth or fact

Abstract: Helicobacter pylori (H. pylori) is one of the most common human bacterial pathogens, and infection causes a wide array of gastric disorders, including simple gastritis, peptic ulcers and gastric malignancies. Gastrointestinal inflammation caused by H. pylori can influence the absorption of glucose and lipids, which are also abnormal in diabetes mellitus. Type 2 diabetes mellitus (T2DM), formerly known as non-insulin-dependent diabetes mellitus or adult-onset diabetes, is a metabolic disorder that is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 152 publications
1
64
3
3
Order By: Relevance
“…However, some studies found a similar or even lower prevalence of H. pylori in diabetics compared with non-diabetic controls (14)(15)(16)(17). The mixed results are likely due to the inconsistency in the methods adopted to define H. pylori activity, diabetes status and differences in sample size.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, some studies found a similar or even lower prevalence of H. pylori in diabetics compared with non-diabetic controls (14)(15)(16)(17). The mixed results are likely due to the inconsistency in the methods adopted to define H. pylori activity, diabetes status and differences in sample size.…”
Section: Discussionmentioning
confidence: 76%
“…However, there are also contradictory reports of H. pylori prevalence in diabetic patients compared to control subjects (14)(15)(16)(17). Limited comparative studies are available for H. pylori infection and diabetic nephropathy particularly in advanced nephropathy associated with proteinuria (18).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of H.pylori infection in patients with diabetes, glucose and lipid absorption is affected by gastrointestinal inflammation induced by H.pylori that may be a risk factor for ensuring blood glucose regulation in diabetic patients 58 . The presence of H.pylori infection in diabetic individuals is associated with microalbuminuria and albumin/creatinine ratio 59 .…”
Section: Relationships With Other Diseases Of Hpylori Infectionmentioning
confidence: 99%
“…While ghrelin otherwise serves lowering the energy expenditure and cause weight gain. 4 Various studies reported that Helicobacter pylori infection in the stomach can increase the production of leptin and decrease the production of ghrelin, which can lead to obesity and diabetes mellitus. 5 In chronic gastritis associated Helicobacter pylori, it was found that the levels of ghrelin was low.…”
mentioning
confidence: 99%
“…Ghrelin and leptin plays a role in energy homeostasis. 4 Leptin is produced by the adipocyte cells, serves to reduce the food intake and increase energy expenditure. While ghrelin otherwise serves lowering the energy expenditure and cause weight gain.…”
mentioning
confidence: 99%